139 Effects of Losartan on Glandular Epithelial Prostatic Hyperplasia in Spontaneously Hypertensive Rats. (1st May 2022) - Shimizu, S; Nagao, Y; Shimizu, T; Higashi, Y; Aratake, T; Zou, S; Yamamoto, M; Saito, M
ABSTRACT: Introduction: Benign prostatic hyperplasia (BPH) and benign prostatic enlargement (BPE) are common disorders in aging men and cause lower urinary tract symptoms. Hypertension induces atherosclerosis in the blood vessels of the lower urinary tract, subsequently following by the development of BPH and BPE. Clinical study demonstrated that anti-hypertensive drug angiotensin II type 1 receptor blocker (ARB) treatment improved storage and voiding scores in male patients with hypertension, whereas other antihypertensive drugs were not effective. ARB could improve prostatic hyperplasia independent of reducing blood pressure. Spontaneously hypertensive rats (SHRs) are widely used as genetically hypertensive model. SHRs also demonstrate decreased prostatic blood flow and develop glandular epithelial hyperplasia and morphological abnormalities in the ventral prostate. Objective: We examined the effects of an ARB, losartan on glandular epithelial prostatic hyperplasia in SHRs. Methods: Thirty-six-weeks old male SHRs were orally treated with losartan (3 or 10 mg/kg/day) or vehicle once daily for 18 weeks. Wistar Kyoto rats (WKYs) were treated with vehicle were used as controls (n = 8). After the oral treatment, effects of losartan were evaluated by measuring prostate weight, blood pressure, and prostatic blood flow. The tissue levels of malondialdehyde (oxidative stress marker; MDA), interleukin-6 (inflammatory cytokine; IL-6), and basic fibroblast growth factor (bFGF) levels in ventral prostate were measured by colorimetric assay and ELISA assay. Histological analysis for the ventral prostate was performed by hematoxylin and eosin (HE) staining and TdT-mediated dUTP nick-end labeling (TUNEL) assay. The glandular epithelial area was determined by HE staining. TUNEL assay was performed to quantify the degree of apoptosis. The statistical differences were determined using one-way analysis of variance followed by the Tukey-Kramer test. Histological data were analyzed using the nonparametric Kruskal-Wallis test followed by the Mann-Whitney U test with Bonferroni's correction for multiple comparison. Results: Body weight did not significantly differ among the groups. The vehicle treated SHRs had significantly higher prostate weight, prostate weight/body weight ratio (PBR), blood pressure, glandular epithelial area, and tissue MDA, IL-6, and bFGF levels in the ventral prostate and lower prostatic blood flow compared to the vehicle treated WKYs. Treatment with losartan significantly decreased PBR and improved prostatic blood flow and glandular epithelial area as well as tissue MDA, IL-6, and bFGF levels in the SHR ventral prostate without affecting blood pressure. High-dose losartan significantly decreased blood pressure and increased TUNEL-positive cells in the ventral prostate in SHRs. Conclusion: Chronic losartan treatment could improve glandular epithelial prostatic hyperplasia via recovery of reduced prostatic blood flow and induction of apoptosis in the ventral prostate in SHRs. Losartan might improve not only hypertension but also prostatic hyperplasia in humans. Disclosure: Work supported by industry: no.